Coupling of dislocations and precipitates: Impact on the mechanical behavior of ultrafine grained Al–Zn–Mg alloys - Ma, Kaka; Hu, Tao; Yang, Hanry; Topping, Troy; Yousefiani, Ali; Lavernia, Enrique J.; Schoenung, Julie M. (Acta materialia, 2016)
Intragranular coupling of dislocations and precipitates is accomplished in an ultrafine grained aluminum 7000 series alloy through a unique thermo-mechanical processing route that involves high strain rate extrusion at ambient temperature as the last step. The as-extruded materials also exhibited a unique bimodal microstructure consisting of: (1) elongated lamellar grains with dimensions of ∼1 μm consisting of sub-grains via low angle grain boundaries, and (2) ultrafine grains approximately ∼100 nm in size with high angle grain boundaries. Our investigation shows that coupling of dislocations and precipitates within the ultrafine grains has a beneficial impact on the mechanical behavior, and results in an extremely high strength, i.e., ultimate tensile strength ∼878 MPa, with uniform elongation of 4.1% strain at fracture. Interestingly, the T6 temper leads to a decrease in strength for the ultrafine grained material with intragranular dislocations while it enhances ductility, which is opposite the behavior observed in the ultrafine grained material that does not contain a high density of intragranular dislocations. This phenomenon is attributed to the loss in dislocation strengthening and grain boundary strengthening, which could not be compensated for by the strength increase due to precipitation. The underlying mechanisms are discussed on the basis of in-situ heating in a transmission electron microscope, theoretical analysis of diffusion controlled precipitation and microstructure characterization, including transmission Kikuchi diffraction. [Display omitted]